Habitat use and population density of proboscis monkeys (nasalis larvatus) at samunsam wildlife sanctuary, Sarawak - Joshua Juan, George Pandong. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A research was conducted at Samunsam Wildlife Sanctuary during the month of August and November 2004 to study the habitat use and population density of proboscis monkeys (Nasalis larvatus). Results indicated that there were distinct differences in the range of habitat use between August and November 2004 with the abrupt expansion from 0.5 km in the month of August to 3 km of different habitat types used in November. The major type of habitat utilized by proboscis monkeys was the mangrove forest. A mixture of mangrove, mixed dipterocarp and tropical heath forest were also used during both seasons. Towards November 2004, the tropical heath-riverine forest habitat was utilized as a result of higher availability of young leaves during this season. Comparison of proboscis monkey density sightings between August and November 2004 showed a distinct difference with only 0.08 groups/ km surveyed in August compared with 0.27 groups/ km surveyed during November 2004. Sightings of individual density showed 0.48 individuals/ km surveyed in the month of August whereas 1.34 individuals/ km surveyed in November 2004. Chi-square (l) test was calculated and showed that there were significant differences (p < 0.05) between both seasons in the no. of group and individual sighted. Sightings of proboscis monkeys were probably influenced by food availability and competition for food resources.